Challenges facing the Limpopo Department of Public Works with regard to service delivery : a case of the core functions of the Department - Kaseke, Lindelani Linda (University of Limpopo (Turfloop Campus), 2011)
The study deals with the service delivery challenges facing the Limpopo Department of Public Works with regard to the discharging of its mandates “Provision of government infrastructure, management and maintenance of government immovable assets”. Literature review was conducted as a secondary source of information and primary information was collected from a sample of 61 respondents. The study used both qualitative (focus group discussions) and quantitative (questionnaires) in data collection and analysis. The findings revealed that the root causes of the challenges and the challenges themselves that the Department of Public Works: Limpopo is facing are internal and are as follows; Unavailability of work tools, low morale, budget constraints, long supply chain management processes and a lack of skilled personnel. Recommendations for these challenges are developing human resource capacity coupled with a good human resource plan, availability of a proper budget, business process reengineering, the introduction of a monitoring and evaluation system, a customer relationship management system and lastly a change of the organisational culture.
Thesis (MPA) --University of Limpopo, 2011
Keywords: Local government; Municipal services; Local government -- South Africa; Municipal services -- South Africa